Unraveling the Intercultural Sensitivity of Foreign Teachers: A Cross-Sectional Examination in Secondary Education across Public and Private Schools, Thailand - Engchuan, Karansupamas; Pengloon, Pong-Ek; Yenphech, Chaleomkiet; Phoowong, Suphakit; Som-In, Somyong (International Journal of Membrane Science and Technology, 2023)
This research aims to explore cultural distinctions and investigate the adaptability of foreign teachers in both public and private secondary schools. A mixed methods approach was employed, utilizing semi-structured interviews and questionnaires as study instruments. The study instruments included the Self-Perceived Communication Competence Scale (SPCC), Intercultural Sensitivity Scale (ISS), and Tromso Social Intelligence Scale (TSIS). Data analysis relied on descriptive statistics. The findings revealed that foreign teachers in both public and private secondary schools demonstrated the highest levels in three key factors: Friends, Interaction Attention, and Social Information Processing. These factors corresponded to self-perceived communication competence, self-reported intercultural sensitivity, and social intelligence, respectively.